Analisis Jangkauan (Outreach) LKMS bagi Rumahtangga Miskin Sektor Pertanian di Perdesaan Bogor, Jawa Barat - Yani Mulyaningsih; Nunung Nuryartono; Rina Oktaviani; Carunia Mulya Firdausy (Institut Pertanian Bogor, 2015)
The Objective of research to acknowledge the hypothesis: outreach islamic microfinance for the poor household of agricultural sector at rural Bogor West Java. The majority of the poor community in Indonesia stay at rural areas. Lack of access credit/financing generally seen as one of the main reasons why many people remain poor. Credit/financing as a powerful instrument to help poor people break out of the vicious cycle because it has the potential to improve income and savings, consequently, enhance capital accumulation, and reinforce high incomes, but providing credit to the poor of agricultural sector in many cases is a very costly activity. Bank isn’t interest to serve it. Hopefully, islamic microfinance institutions reaches to more the poor of agricultural sector. The average loan is the most commonly used to measure the degree of microfinance institutions (MFIs) outreach to poor customer segments, but it is very simple. Using the CGAP (Consultative Group to assist the poorest) method, the poverty multidimension of islamic microfinance outreach was measured. The result of study showed that islamic MFIs didn’t reach the poor household of agricultural sector at rural Bogor West Java.